Ex vivo osteochondral test system with control over cartilage defect depth – A pilot study to investigate the effect of oxygen tension and chondrocyte based treatments in chondral and full thickness defects in an organ model. Issue 2 (June 2021) - Schwab, Andrea; Buss, Alexa; Pullig, Oliver; Ehlicke, Franziska
Abstract: Objective: Cartilage defect treatment strategies are dependent on the lesion size and severity. Osteochondral explant models are a platform to test cartilage repair strategies ex vivo . Current models lack in mimicking the variety of clinically relevant defect scenarios. In this controlled laboratory study, an automated device (artificial tissue cutter, ARTcut®) was implemented to reproducibly create cartilage defects with controlled depth. In a pilot study, the effect of cartilage defect depth and oxygen tension on cartilage repair was investigated. Design: Osteochondral explants were isolated from porcine condyles. 4 ​mm chondral and full thickness defects were treated with either porcine chondrocytes (CHON) or co-culture of 20% CHON and 80% MSCs (MIX) embedded in collagen hydrogel. Explants were cultured with tissue specific media (without TGF-β) under normoxia (20% O2 ) and physiological hypoxia (2% O2 ). After 28 days, immune-histological stainings (collagen II and X, aggrecan) were scored (modified Bern score, 3 independent scorer) to quantitatively compare treatment outcome. Results: ARTcut® represents a software-controlled device for creation of uniform cartilage defects. Comparing the scoring results of the MIX and the CHON treatment, a positive relation between oxygen tension and defect depth was observed. Low oxygen tension stimulated cartilaginous matrix deposition in MIX group in chondral defects and CHON treatment in full thickness defects. Conclusion: ARTcut® has proved a powerful tool to create cartilage defects and thus opens a wide range of novel applications of the osteochondral model, including the relation between oxygen tension and defect depth on cartilage repair.